2008
DOI: 10.1529/biophysj.107.125542
|View full text |Cite
|
Sign up to set email alerts
|

The Mycobacterium tuberculosis Virulence Factor Trehalose Dimycolate Imparts Desiccation Resistance to Model Mycobacterial Membranes

Abstract: Mycobacteria, including persistent pathogens like Mycobacterium tuberculosis, have an unusual membrane structure in which, outside the plasma membrane, a nonfluid hydrophobic fatty acid layer supports a fluid monolayer rich in glycolipids such as trehalose 6,6'-dimycolate (TDM; cord factor). Given the abilities of mycobacteria to survive desiccation and trehalose in solution to protect biomolecules and whole organisms during freezing, drying, and other stresses, we hypothesized that TDM alone may suffice to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 50 publications
2
56
0
Order By: Relevance
“…Supported monolayers consisting of 0.99-X:X:0.01, DOPC:trehalose glycolipid:Texas Red DHPE were deposited using the supported monolayer architecture used for earlier investigations of TDM (12), described also in Materials and Methods. (See Materials and Methods for lipid abbreviations.)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Supported monolayers consisting of 0.99-X:X:0.01, DOPC:trehalose glycolipid:Texas Red DHPE were deposited using the supported monolayer architecture used for earlier investigations of TDM (12), described also in Materials and Methods. (See Materials and Methods for lipid abbreviations.)…”
Section: Resultsmentioning
confidence: 99%
“…Motivated by this, and by the uniqueness of trehalose glycolipids in the mycobacteria, we recently examined whether TDM can confer stress resistance to lipid membranes of which it is a component. Using an experimental model of mycobacterial membrane structure that allows control of molecular composition (Figure 2), we found that TDM does confer dehydration resistance to membranes, and can do so even as a minority membrane component (12). To the best of our knowledge, this was the first reported discovery of a dehydration-resistant lipid.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cord factor is a constituent of the outer lipid layer of the bacterial cell wall [12] . One of the presumable functions of the cord factor is to protect the bacteria from desiccation by stabilizing the physicochemical properties of the lipid layer and keeping it intact upon drying [13] . We have investigated the kinetics of the synthesis of maradolipids over the course of the development of dauer larva.…”
mentioning
confidence: 99%